PENGARUH STRATEGI PROMOSI DAN KUALITAS PELAYANAN TERHADAP KEPUASAN NASABAH PADA PT. BNI (PERSERO) Tbk KANTOR CABANG BOYOLALI - Pawestri Panglipurati; Listyowati Puji Rahayu; Unna Ria Safitri (EKOBIS, 2023)
One of the main problems of financial institutions is in the promotion strategy and customer satisfaction. Therefore, Bank BNI Boyolali Branch Office is required to always maintain product, trust and customer satisfaction by improving service quality so that customer satisfaction increases, it is necessary to carefully determine consumer needs in an effort to meet expectations or desires and increase satisfaction with promotions and services provided. This study aims to analyze the promotion strategy and service quality on customer satisfaction at Bank BNI Boyolali Branch Office either simultaneously or partially. This study uses quantitative descriptive which is intended to test the truth of the theory with field observations and explain the results of research on how things are happening in the field.Data collection techniques were carried out through interviews, questionnaires, and observations. Data analysis techniques used quantitative techniques with a statistical approach, namely normality test, classical assumption test, multiple linear regression analysis and correlation coefficient analysis.The results of the study show, This shows that the promotion strategy variable partially affects customer satisfaction, in other words the promotion strategy variable has a significant influence on customer satisfaction and the service quality variable partially affects customer satisfaction, in other words the service quality variable has a significant influence. to customer satisfaction. Keywords: Promotion Strategy, Service Quality, and Customer Satisfaction